2014
DOI: 10.1097/lgt.0b013e31829706bc
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Intraepithelial Neoplasias of the Lower Female Genital Tract

Abstract: Our results support the hypothesis that a positive HPV-mRNA test could be a marker of persistent infection and a risk factor for the onset of metachronous lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In addition, in high-grade lesions subgroup, more than half (53.3%) of the patients were HPV16 infection. Consistent with the second pathogenesis theory and previous study [ 5 ], in this study, multiple HPV infections were an independent risk factor for multicentric lesions. However, multiple HPV infections did not significantly increase the risk of high-grade lesion beyond that for the highest-risk type found [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In addition, in high-grade lesions subgroup, more than half (53.3%) of the patients were HPV16 infection. Consistent with the second pathogenesis theory and previous study [ 5 ], in this study, multiple HPV infections were an independent risk factor for multicentric lesions. However, multiple HPV infections did not significantly increase the risk of high-grade lesion beyond that for the highest-risk type found [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…The average age of patients with multicentric lesions has not been consistent in previous studies, ranged from 36.3 to 43 years [ 3 5 , 13 ]. In this study, the median age of patients with multicentric lesions was higher than that reported in the previous literatures.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations